Forecasting Forest Vulnerability to Drought in Pyrenean Silver Fir Forests Showing Dieback - Gazol, Antonio; Sangüesa-Barreda, Gabriel; Camarero, J. Julio (Frontiers in Forests and Global Change, 2020)
Forest dieback is manifested as widespread loss of tree vigour, growth decline and high mortality rates. Forest dieback is becoming increasingly frequent and extended, particularly in drought-prone regions. This is the case of the south-western Spanish Pyrenees, where keystone species such as Silver fir reach their xeric and southern distribution limits. While dieback of this species has been widely documented in this area, we still lack methodologies to forecast the vulnerability of these forests in response to increasing drought stress so as to anticipate their potential dieback in the future. Here we study multiple features of Silver fir forest and trees to evaluate whether previous growth rates and their growth trends are valid predictors of forest dieback. Further, we validate our methodology revisiting two Silver fir sites sampled two decades ago. The defoliation degree was strongly related with radial growth, and growth trends differed between moderately to highly defoliated trees and non-defoliated trees. Forests showing dieback, i.e. those in which 25% of the sampled trees showing defoliation > 50%, were located at low elevation and received less rainfall in summer than forests showing no dieback. Trees showing high defoliation presented lower growth rates than non-defoliated trees. Moreover, we ratified that defoliation has increased considerably over the last two decades in one of the two revisited sites, but we were unable to accurately forecast growth trends in both sites, particularly in the site not showing dieback. The retrospective assessment of growth rates and trends offers valuable information on the vulnerability of Silver fir trees to drought. However, we are still far from being able to forecast the vulnerability of Silver fir forest to increasing drought. A systematic monitoring of growth across a wide tree-ring network of sites might provide valuable information to advance in this direction.